1993
DOI: 10.1002/mds.870080317
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of clozapine on levodopa response in parkinson's disease: A preliminary study

Abstract: Clozapine has been shown not only to be effective in ameliorating dopaminomimetic psychosis but to improve parkinsonian symptomatology. Six parkinsonian patients with motor fluctuations under levodopa treatment and severe interdose "off" periods (believed to be mediated by an inhibitory effect of subthreshold levels of levodopa) underwent a trial of clozapine. The effects of this drug on levodopa response were measured by means of an acute levodopa test both before and after receiving clozapine. After 1 month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 12 publications
1
25
1
Order By: Relevance
“…Furthermore, tardive dyskinesia associated with the prolonged use and subsequent withdrawal of conventional antipsychotic agents is suppressed by high doses of clozapine given over extended periods (Shopsin et al 1979;Kane et al 1988). It has also been reported that clozapine has a beneficial effect on tremor in Parkinson's disease patients (Erevalo and Gershanik 1993). Taken together, these findings suggest that the lack of EPS seen with clozapine may be a consequence of the ability of the compound, at least in part, to suppress its own induction of EPS.…”
Section: Introductionsupporting
confidence: 57%
“…Furthermore, tardive dyskinesia associated with the prolonged use and subsequent withdrawal of conventional antipsychotic agents is suppressed by high doses of clozapine given over extended periods (Shopsin et al 1979;Kane et al 1988). It has also been reported that clozapine has a beneficial effect on tremor in Parkinson's disease patients (Erevalo and Gershanik 1993). Taken together, these findings suggest that the lack of EPS seen with clozapine may be a consequence of the ability of the compound, at least in part, to suppress its own induction of EPS.…”
Section: Introductionsupporting
confidence: 57%
“…Additionally, clozapine has been shown to reduce symptoms of tardive dyskinesia (Safferman et al 1991) and Meige syndrome (Van Putten et al 1990). Recent evidence indicates that clozapine is effective at ameliorating motor dysfunctions in patients with idiopathic Parkinson's disease (Pakkenberg and Pakkenberg 1986;Bernardi and Del Zompo 1990;Fisher et al 1990;Friedman and Lannon 1990;Arevalo and Gershanik 1993). The antiparkinsonian effects of clozapine can occur at doses that are somewhat lower than those used to treat psychotic patients (e.g., 12.5-25 mg; Friedman and Lannon 1990;Arevalo and Gershanik 1993).…”
Section: Introductionmentioning
confidence: 97%
“…[17][18][19][20] Interestingly, the ''super off'' phenomenon 21 observed in PD patients with levodopa therapy also improves with CZP as well as parkinsonian tremor and other motor complications and dyskinesias. [22][23][24][25] Regarding the improvement observed in motor function, we cannot establish with certainty if parkinsonian signs were reduced by the action of CZP, withdrawal of neuroleptic drugs, or both at the same time.…”
Section: Discussionmentioning
confidence: 99%